Pengenalan Akuntansi Syariah Guna Meningkatkan Kompetensi Siswa/I dan Guru SMK Jurusan Akuntansi - Nurul Fauziyyah; Ilham Ramadhan Ersyafdi; Fitriah Ulfah (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2022)
This paper provides an overview of the implementation of community service carried out at SMK Bina Harapan Ciseeng. This community service is carried out in order to improve the competence of vocational students and teachers, especially the accounting department by providing an introduction to sharia accounting for students of SMK Bina Harapan Ciseeng. This Paper is a description Paper captured a series of preparatory activities and during the community service agenda. This activity was carried out targeting students and teachers at SMK Bina Harapan Ciseeng and the implementation is divided into several sessions. The summary of this community service is that it is a need to improve competence regarding sharia accounting among these students so that students' interest in sharia accounting can be accomodated and competencies related to industrial needs can be channeled through competent graduates in their fields.